Deuterium‐reinforced linoleic acid lowers lipid peroxidation and mitigates cognitive impairment in the Q140 knock in mouse model of Huntington's disease. (7th July 2018) - Hatami, Asa; Zhu, Chunni; Relaño‐Gines, Aroa; Elias, Chris; Galstyan, Arpine; Jun, Michael; Milne, Ginger; Cantor, Charles R.; Chesselet, Marie‐Francoise; Shchepinov, Mikhail S.
Abstract : Huntington's disease (HD) is an autosomal dominant neurodegenerative disease which has no effective treatment and is characterized by psychiatric disorders, motor alterations, and dementia, with the cognitive deficits representing a devastating aspect of the disorder. Oxidative stress and elevated levels of lipid peroxidation (LPO) products are found in mouse models and patients with HD, suggesting that strategies to reduce LPO may be beneficial in HD. In contrast with traditional antioxidants, substituting hydrogen with deuterium at bis‐allylic sites in polyunsaturated fatty acids (D‐PUFA) decreases the rate‐limiting initiation step of PUFA autoxidation, a strategy that has shown benefits in other neurodegenerative diseases. Here, we investigated the effect of D‐PUFA treatment in a knock‐in mouse model of HD (Q140) which presents motor deficits and neuropathology from a few months of age, and progressive cognitive decline. Q140 knock‐in mice were fed a diet containing either D‐ or H‐PUFAs for 5 months starting at 1 month of age. D‐PUFA treatment significantly decreased F2 ‐isoprostanes in the striatum by approximately 80% as compared to H‐PUFA treatment and improved performance in novel object recognition tests, without significantly changing motor deficits or huntingtin aggregation. Therefore, D‐PUFA administration represents a promising new strategy to broadly reduce rates of LPO, and may be useful in improving a subset of the core deficits in HD. Abstract : Lipid peroxidation (LPO) is an important factor in Huntington's disease (HD) pathogenesis. Deuterated polyunsaturated fatty acids (D‐PUFAs) are resistant to LPO because of the isotope effect on the rate‐limiting step. A diet containing D‐PUFAs in Q140 KI mice improves cognition and memory by decreasing LPO, thus representing a promising new strategy to reduce LPO, and combat cognitive decline in HD.